Deconstruction of Genre in the Novel Rabies by Borislav Pekić - Vladušić, Slobodan V. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The self-poetic statements of Daniel Leverkin were examined in this paper. It is going to be revealed that exactly this component of Rabies puts under question simple genre entry of this novel. Poetical thought in this novel has its consistency: it leads from testimony towards the story that has to put this testimony into context, in order to confirm its humanistic orientation. In this insufficiency of testimony and the need for the story, we recognise the key difference between aesthetics of testimony in Kiš, and fictionalisation of testimony in Pekić. In the second part of the paper, the motif of Leverkin’s interruption of writing of his self-poetic journal and the character of Gabriel who is Leverkin’s successor was analysed in the context of interruption of writing that is being thematized in Andrić’s Omerpasa Latas, and Crnjanski’s strive by the means of count Rjepnin’s suicide (in Novel of London).